Peran Produk Wisata dan Citra Destinasi terhadap Keputusan Berkunjung Wisatawan - Safitri, Indri; Ramdan, Asep M.; Sunarya, Erry (Jurnal Ilmu Manajemen, 2020)
The purpose of this study is to determine the role of tourism products and destination image of tourists visiting decision. The method in this study uses a type of probability sampling, including simple random sampling with a sample of 200 respondents. The analysis technique used is multiple linier regression analysis, coefficient of determination, simultaneous model testing (F test), and partial hypothesis testing (T test). T test result shower that tourism products had a positive and significant effect on visiting decisions, destination image had a positive and significant effect on visiting decisions.The F test results the probability value sig. 0,000 < 0,05 which means that the F test can be accepted and shows the influence simultaneously. Based on the results of the coefficient of determination test obtained a value of 0,596 can be interpreted that the influence of tourism products and destination image on the decision of visiting that is equal to 59,6%, the remaining 40,4 % is influenced by other factors not explained this study. Â